WOMEN ENTREPRENEURS IN INDIA: CHALLENGES, OPPORTUNITIES, AND FUTURE PROSPECTS - Chopra, Sunita; Sushmana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Entrepreneurs play a significant role in economic development of the country. Entrepreneurs use their innovative skills to turn their ideas into business prospects .Entrepreneurs determine a country’s economic growth by creating new job opportunities ,expanding employment opportunities, supplying products and services and producing taxes for the government. Capital formation is largely possible only by entrepreneurship programme. The entrepreneurs are in important place in generating economic and social development for the country. Both the Central and State government have been launched various schemes for encouraging entrepreneurship in the country. In India, male is dominating the society. Despite this, women make their position in every field .Women entrepreneurs are steadily gaining the position and contributing their share in GDP of the country. However, Women in India and around the world face numerous problems and challenges at every stages of business idea.This paper explores the evolution of women entrepreneurship in India, analyzing their contribution to economic growth, what problems and challenges are faced by new and existing women entrepreneurs , what future prospects are available in entrepreneurship and the support mechanisms available to them. It also examines successful case studies of women entrepreneurs.